A multifunctional silicon-containing hyperbranched epoxy: controlled synthesis, toughening bismaleimide and fluorescent properties. Issue 28 (4th July 2016) - Niu, Song; Yan, Hongxia; Li, Song; Tang, Cheng; Chen, Zhengyan; Zhi, Xiaoli; Xu, Peilun
Abstract : A multifunctional silicon-containing hyperbranched epoxy is explored. The polymer can not only toughen BMI resins, but also emit blue photoluminescence. Abstract : A novel silicon-containing hyperbranched epoxy (SHBEp) has been explored via a one-pot A2 + B3 polycondensation reaction using (3-glycidyloxypropyl)trimethoxysilane (A-187) and excess neopentyl glycol (NPG) under solvent-free and catalyst-free conditions. We investigate for the first time bismaleimide (BMI) toughening effect using the fabricated polymer, and a series of SHBEp/BMI thermosets are then constructed, and then their mechanical properties like impact strength, flexural strength, and thermal stability are studied; meanwhile the toughening effect of SHBEp and conventional epoxy resin E51 is also compared. The results indicate that a proper addition of SHBEp (8 wt%) can significantly improve the toughness and thermal performance of thermosets compared to E51 with the same content. It is, therefore, revealed that the polymer is promising to act as an effective BMI toughener. Unexpectedly, a bright blue photoluminescence is observed when the SHBEp is excited under 365 nm UV light, and its average fluorescence lifetime and absolute fluorescence quantum yield are 4.30 ns and 4.61% respectively. It is demonstrated by our primary investigation that the epoxide and hydroxyl groups simultaneously help the light emission. Thus, the SHBEp bearing unconventional chromophores is also particularly expected to be a new light-emitting material.